ANALYSIS OF GOVERNANCE, EXTERNAL GUARANTEE, COMPANY CHARACTERISTICS AND RESURRECTION SUSTAINABILITY REPORT - Malau, Melinda (Research In Management and Accounting (RIMA), 2018)
Thie research purpose to analyze the governance, external assurance, firm-level characteristics and financial distress on the sustainability reporting. The method used in this study is multiple regression analysis using Eviews 9. The samples used in this research are 242 which the data of 121 manufacturing companies listed on the Indonesia Stock Exchange from 2014-2015. The result shows that the governance committee, the sustainability report of the assurance provider, the number of members on the audit committee and the number of members on the board of directors as firm-level characteristics have a significant positive effect on sustainability reporting. Financial distress has a significant negative effect on sustainability reporting. Operating cash flow has no significant effect on sustainability reporting, whereas log total assets have a significant positive effect on sustainability reporting